Correction: Epstein-Barr virus nuclear antigen EBNA-LP is essential for transforming naive B cells, and facilitates recruitment of transcription factors to the viral genome - Szymula,A; Palermo,RD; Bayoumy,A; Groves,IJ; Abdullah,MB; Holder,B; White,RE (PLoS Pathogens, 2019)
In the original submission, the negative control in ChIP experiments was misidentified as detecting the myoglobin promoter: it in fact detects the myogenin promoter. As a result, there are textual errors in the captions for Fig 8, “Binding of EBNA2 to viral and host loci is influenced by EBNA-LP,” and Fig 9, “EBNA-LP enhances binding of host transcription factors RBPJ and EBF1 to viral but not host promoters.” There is also an ambiguity in the second table in the S3 Table file that has been clarified.